Strategi Peningkatan Kualitas Produk Dan Kepuasan Konsumen Sate Lilit Ayam Men Budi Di Desa Blahkiuh Kabupaten Badung Provinsi Bali - Suputra, I Gede Maha Adijaya; Mertayasa, I Made; Wrasiati, Luh Putu; Yoga, I Wayan Gede Sedana; Gunam, Ida Bagus Wayan (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2026)
In the village of Blahkiuh, located in the Abiansemal sub-district, Badung regency, there are many sellers of traditional foods. One of the traditional food sellers there is Men Budi. He sells traditional chicken sate lilit. The intense business competition has led business owners to change their marketing strategies by improving product quality and analyzing consumer importance and satisfaction. This study aimed to assess the quality attributes of chicken sate lilit, importance and satisfaction levels,and develop strategies to enhance the of Men Budi's chicken sate lilit. The Quality Function Deployment (QFD) method was employed for the analysis. The findings identified eight quality attributes of chiken sate lilit that were important and satisfactory to consumers: taste, texture, size, price, packaging, cleanliness, aroma, and color. Taste received the highest consumer importance ranting (4.53), while aroma and color scored the lowest (4.18). in terms of satisfaction, aroma ranked the highest (4.31), while texture was rated the lowest (3.95). Improvement priorities included texture, price, cleanliness, color, and taste. Additionally, technical parameters requiring attention were mixing, grilling, and raw material preparation.